PENGARUH PAD, PMDN, TENAGA KERJA DAN IPM TERHADAP PERTUMBUHAN EKONOMI KABUPATEN/KOTA PROVINSI BALI - krhisna bela, Gede Bayu; Djinar Setiawina, Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 9 No 6 (2020): VOL 9 NO 6, JUNI 2020, PP 1200-1430, 2020)
ABSTRACT This study aims to analyze the influence of PAD, PMDN, Labor and HDI simultaneously and partially on Economic Growth in Bali Province 2010-2016. The data used in this study is secondary data. The method of data collection is a method of non-participant observation, namely by looking for data from the Central Statistics Agency, the Investment Board and other relevant agencies. The analysis technique used is multiple linear regression analysis. The results of the SPSS test obtained simultaneous results of PAD, PMDN, Labor, and IPM variables that significantly affected the Regency / City Economic Growth in Bali Province 2010-2016. Partially PAD, PMDN, Labor, and IPM have a positive and significant effect on Regency / City Economic Growth in Bali Province 2010-2016. That is, the higher the PAD, PMDN, Labor and HDI in a Regency / City area, the economic growth also increases. Keywords: economic growth, PAD, PMDN, labor, HDI